2020 IEEE International Symposium on Multimedia (ISM) 2020
DOI: 10.1109/ism.2020.00007
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of RTC applications

Abstract: Real-Time Communication (RTC) applications have become ubiquitous and are nowadays fundamental for people to communicate with friends and relatives, as well as for enterprises to allow remote working and save travel costs. Countless competing platforms differ in the ease of use, features they implement, supported user equipment and targeted audience (consumer of business). However, there is no standard protocol or interoperability mechanism. This picture complicates the traffic management, making it hard to is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…Investigating this asymmetry further, we discovered an interesting phenomenon: We found that Zoom uses a relay server instead of direct communication. Additionally, related work by Nistico et al [21] suggests that Zoom uses Forward Error Correction (FEC) for error recovery. This is further supported by a related patent from Zoom itself, which talks about a methodology to generate FEC data at the server [17].…”
Section: Network Utilizationmentioning
confidence: 99%
See 3 more Smart Citations
“…Investigating this asymmetry further, we discovered an interesting phenomenon: We found that Zoom uses a relay server instead of direct communication. Additionally, related work by Nistico et al [21] suggests that Zoom uses Forward Error Correction (FEC) for error recovery. This is further supported by a related patent from Zoom itself, which talks about a methodology to generate FEC data at the server [17].…”
Section: Network Utilizationmentioning
confidence: 99%
“…Specifically, the network utilization with constrained downstream throughput (< 0.8 Mbps) is only 39-70% (Figure 1b), while it is more than 90% in the case of a constrained uplink (Figure 1a). Upon further exploration, we discovered that Meet also uses a relay server, as well as simulcast, wherein the sender (C2) transmits multiple copies of the video to the server, each at a different quality level [21]. The server then relays one of the quality streams to C1 depending on the inferred available capacity of the server-C1 link.…”
Section: Network Utilizationmentioning
confidence: 99%
See 2 more Smart Citations
“…Leveraging these data, we show which protocols that each application adopts for streaming multimedia content, the volume of traffic that they generate, and the servers and domains that they contact (for brevity, we use, throughout the paper, the term domain referring to the fully qualified domain name). We show that Stadia and GeForce Now adopt the standard real-time protocol (RTP) for streaming [3], largely adopted by real-time communication applications [4], while PS Now uses an undocumented protocol or encapsulation mechanism. Stadia and GeForce Now transmit video up to 45 Mbit/s, while PS Now does not exceed 13 Mbit/s.…”
Section: Introductionmentioning
confidence: 99%